Association between antihypertensive medication use and kidney cancer risk: a meta-analysis accounting for hypertension - Jung, Minji; Li, Mingyi; Shin, Jaekyu; Chung, Benjamin I.; Langston, Marvin E. (BMC cancer, 2025)
Evidence that antihypertensive medication (AHTN) use is associated with an increased risk of kidney cancer (KC) is emerging. However, limited evidence is available on disentangling the effects of AHTN use on KC from hypertension, which is a risk factor for KC. We aimed to identify pooled estimates for the associations between AHTN use and KC risk, independent of hypertension. We searched for observational studies that investigated the associations between AHTN use and KC through January 2025. To identify the independent effects of AHTN from hypertension, we conducted stratified analyses with and without accounting for hypertension: any methods (matching, adjustment, or stratification/restriction) versus none. We conducted random-effects meta-analyses with robust variance estimation to calculate pooled relative risk (RR). In this meta-analysis consisting of 39 eligible studies, AHTN use was associated with an increased risk of KC based on estimates that accounted for hypertension (RR 1.19, 95% confidence interval (CI) 0.93-1.52 for angiotensin-converting enzyme inhibitor; RR 1.15, 95% CI 1.00-1.31 for angiotensin receptor blocker; RR 1.09, 95% CI 1.03-1.16 for beta-blocker, RR 1.40, 95% CI 1.12-1.75 for calcium channel blocker (CCB); RR 1.36, 95% CI 1.20-1.55 for diuretic; and RR 1.40, 95% CI 1.13-1.75 for non-classified AHTN). Findings from duration‒response relationships supported the main findings. AHTN use was associated with an increased risk of KC compared to no use, even after accounting for hypertension, with the highest risk observed for CCB. Our findings highlight the potential KC risks associated with different AHTN classes, with optimal cardiovascular care remaining an important consideration.